1997
DOI: 10.1128/jvi.71.3.1984-1991.1997
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's sarcoma-associated herpesvirus encodes a functional cyclin

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) (also called human herpesvirus 8) is consistently found in Kaposi's sarcoma lesions and in body-cavity-based lymphomas. A 17-kb KSHV lambda clone was obtained directly from a Kaposi's sarcoma lesion. DNA sequence analysis of this clone identified an open reading frame which has 32% amino acid identity and 53% similarity to the virus-encoded cyclin (v-cyclin) of herpesvirus saimiri (HVS) and 31% identity and 53% similarity to human cellular cyclin D2. This KSHV ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(100 citation statements)
references
References 47 publications
2
94
0
3
Order By: Relevance
“…Previous results had already shown that the BGLF4 protein phosphorylates histones in in vitro kinase assays [206]. In fact, there are several examples of viral kinases capable of histone (usually H1 or H2B) phosphorylation in vitro, including HCMV UL97 [207], human herpesvirus 6 U69 [208], HSV-2 UL13 [209] as well as KSHV and MHV-68 viral cyclin/ cyclin-dependent kinase complexes [210][211][212][213]. However, the lack of in vivo data makes any conclusion about the actual relevance of these observations impossible.…”
Section: Histone Phosphorylation and Other Histone Modificationsmentioning
confidence: 98%
“…Previous results had already shown that the BGLF4 protein phosphorylates histones in in vitro kinase assays [206]. In fact, there are several examples of viral kinases capable of histone (usually H1 or H2B) phosphorylation in vitro, including HCMV UL97 [207], human herpesvirus 6 U69 [208], HSV-2 UL13 [209] as well as KSHV and MHV-68 viral cyclin/ cyclin-dependent kinase complexes [210][211][212][213]. However, the lack of in vivo data makes any conclusion about the actual relevance of these observations impossible.…”
Section: Histone Phosphorylation and Other Histone Modificationsmentioning
confidence: 98%
“…One additional mechanism besides vIL-6 by which HHV8 drives cell proliferation is by the expression of a functional viral cyclin 49 most closely related to human cyclin D (FIG. 1, bottom center).…”
Section: Virus-encoded Cellular Homologues and Their Role In Mitogenementioning
confidence: 99%
“…k-Cyclin (ORF72) is a homolog of cyclin D2 (32% identity and 54% similarity). (38) The predominant partner for k-cyclin is CDK6, and this viral CDK complex phosphorylates RB protein like cellular CDK complexes. (38) Moreover, k-cyclin /CDK6 shows broader substrate specificity than cellular cyclinD/CDK6.…”
Section: Cell Cycle Deregulation By Viral Gene Productsmentioning
confidence: 99%
“…(38) The predominant partner for k-cyclin is CDK6, and this viral CDK complex phosphorylates RB protein like cellular CDK complexes. (38) Moreover, k-cyclin /CDK6 shows broader substrate specificity than cellular cyclinD/CDK6. k-Cyclin / CDK6 can phosphorylate CDK2 substrates, including ORC1, CDC6, p27Kip1, histone H1, and others.…”
Section: Cell Cycle Deregulation By Viral Gene Productsmentioning
confidence: 99%